Solve for \( x \) \( \begin{array}{l}\text { a) } 3,7 x+9,14=0 \\ \text { b) }-2,4 x-8,8=1\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve for \( x \) in both equations, let's tackle them one at a time. For equation \( a) \): \[ 3.7x + 9.14 = 0 \] First, we subtract \( 9.14 \) from both sides: \[ 3.7x = -9.14 \] Next, we divide by \( 3.7 \): \[ x = \frac{-9.14}{3.7} \] Calculating this gives: \[ x \approx -2.47 \] Now for equation \( b) \): \[ -2.4x - 8.8 = 1 \] First, we add \( 8.8 \) to both sides: \[ -2.4x = 1 + 8.8 \] This simplifies to: \[ -2.4x = 9.8 \] Next, we divide by \( -2.4 \): \[ x = \frac{9.8}{-2.4} \] Calculating this gives: \[ x \approx -4.08 \] So the solutions are: a) \( x \approx -2.47 \) b) \( x \approx -4.08 \)